Focused investigations to expedite cancer diagnosis among patients with lymphadenopathy in a tuberculosis and HIV-endemic region. (15th March 2023) - Antel, Katherine; Oosthuizen, Jenna; Brown, Karryn; Malherbe, Francois; Loebenberg, Perry; Seaton, Cylene; Baloyi, Siphiwe; Simba, Kudakwashe; Chetty, Dharshnee; Louw, Vernon J.; Maartens, Gary; Verburgh, Estelle R.
Abstract : Purpose: In tuberculosis (TB)-endemic areas, lymphadenopathy is frequently due to TB adenitis, but lymphoma and cancers are important differential diagnoses and critical to diagnose at the earliest opportunity. Key obstacles to lymphoma diagnosis include empiric TB treatment and difficulty accessing a biopsy. We report on a specialized clinic utilizing high-yield investigations for patients with lymphadenopathy. Methods: This prospective interventional study investigated the utility of a core biopsy and the Xpert MTB/RIF Ultra (Ultra) on fine-needle aspirate (FNA) and tissue in a newly established lymph node biopsy clinic over 4 years. Electronic referral facilitated patient assessment within a week. Hematology fellows without specialist surgical or radiological expertise performed the biopsy on the first visit. Results: In 277 patients, including 43% people with HIV, TB was the most frequent diagnosis (34%), followed by lymphoma (27%) and other cancers (17%). Patients were seen a median of 5 days [interquartile range (IQR) 2–8.5 days] from referral. Core biopsy provided sufficient tissue for diagnosis in 96% of patients with lymphoma (72/75) and 94% of patients with cancer (44/47). FNA Ultra had a sensitivity of 73.9% [34/46; 95% confidence interval (CI) 58.9–85.7], and tissue Ultra 73% (46/63; 95% CI 60.3–83.4). There were six false-positive Ultra tests, highlighting the value of histology to either support TB or make an alternative diagnosis. Conclusion: Core biopsies collected under the conditions described are safe and sensitive and can yield a rapid diagnosis. Combining Ultra and a core biopsy can accurately diagnose TB and cancer. This clinic provides an implementation model for resource-constrained and TB-endemic areas.